High dose chemotherapy followed by autologous hematopoietic stem cell transplantation for advanced germ cell tumors: State of the art and a single-center experience. (January 2022) - Pierantoni, Francesco; Maruzzo, Marco; Bimbatti, Davide; Finotto, Silvia; Marino, Dario; Galiano, Antonella; Basso, Umberto; Zagonel, Vittorina
Highlights: This review analyses the evidence on high dose chemotherapy as salvage therapy for metastatic germ cell tumors. It focuses on the 2-year overall survival, complications, and the quality of life of survivors. The review is integrated by our retrospective real-world experience, with survival and quality of life outcomes. Abstract: Background: Evidence for the choice of second line, standard vs high dose chemotherapy, (SDCT, HDCT) for patients with relapsed germ cell tumors (GCTs) comes mainly from retrospective studies. Material and methods: : relevant literature was reviewed, considering as endpoints both survival and long term quality of life (QoL). Patients with metastatic GCT progressing after first-line treatment at our Institution were retrospectively evaluated. Results: HDCT seems to achieve a higher rate of long-term remissions. QoL data for this group of patients are lacking. Our experience on 29 patients was in line with these results. Two-year OS for the 18 patients treated with one or two HDCT/PBSCT procedures was 47.5 %, while 2-year PFS was 44 %. For the 11 receiving SDCT 2-year OS was 36.4 %, and 2-year PFS was 32.7 %. Conclusions: HDCT/PBSCT confirmed to be effective in treating patients with relapsed GCT, but prospective studies are needed.